Ultrasonic energy in textile processes - (:unkn) unknown (Textile Inst, Manchester, United Kingdom, 1997)
The application of ultrasonic energy on textile processing has a substantial effect on the fixation reaction and increases the color yield of the cellulosic fibers. Ultrasonic power is also used to remove the unfixed reactive dyes in washing off sequences and has a great effect on the washing process. The use of power ultrasound in textile wet processes means energy savings, less water consumption, less processing time and increased dyeing shade and better processing conditions.